Biliary complications among live donors following live donor liver transplantation. Issue 4 (August 2018) - Shaji Mathew, Johns; Manikandan, K.; Santosh Kumar, K.Y.; Binoj, S.T.; Balakrishnan, Dinesh; Gopalakrishnan, Unnikrishnan; Narayana Menon, Ramachandran; Dhar, Puneet; Sudheer, O.V.; Aneesh, S.; Sudhindran, Surendran
Abstract: Introduction: In live donor liver transplantation (LDLT), bile duct division is a critical step in donor hepatectomy. Biliary complications hence are a feared sequelae even among donors. Long term data on biliary complications in donors from India are sparse. Methods: Prospective evaluation of 452 live donors over 10 years was performed to ascertain the incidence & risk factors of clinically significant biliary complications. Results: Of the 452 donor hepatectomies (M: F = 114:338, median age = 38), 66.2% (299) were extended right lobe grafts, 24.1% (109) modified right lobe and 9.7% (44) were left lobe grafts. Portal vein anatomy was Type-I in 85% (386), Type-II in 7.5% (34) and Type-III in 7.1% (32). Following donor hepatectomy, a single bile duct opening occurred only in 46.5% (210) of the grafts. Of the remaining 53.5% grafts, 2 ductal openings were noted in 217 (48%) and three ductal openings in 25 (5.5%). Incidence of multiple openings in the duct were more commonly noted in Type II (70.6%) and III (75%) portal vein anatomy than in grafts with Type I (50.4%) portal anatomy ( P = 0.001) Bile leak was noted in 15 (3.3%) donors which included one broncho-biliary fistula and bilio-pleural fistula. Analysis revealed no association between post-operative biliary complications and type of graft, portal vein anatomy or biliary anatomy. There was a single mortality in this series secondary to biliary sepsis. On long term follow, there were no biliary strictures in any of the patients. Conclusions: Biliary complications although rare (3.3%), present significant peri-operative morbidity to the donors.